Modern Postural Yoga, Meditation, and Spiritual Seeking: Ashtanga Vinyasa Yoga and “Moving Meditation” - Masayuki Ito (Religions)
This study focuses on yoga as part of contemporary spiritual culture (CSC) and examines the relationship between modern yoga and meditation. First, I investigate the purpose of practice and the position of meditation in classical yoga and hatha yoga; I clarify that classical yoga aims to stop the fluctuations of the mind by subduing physical activity, while hatha yoga aims to activate energy by working on the body, which is a microcosm of the universe. Next, I explore the characteristics of modern postural yoga (MPY, which was established in the early 20th century) and how it differs from traditional yoga. Based on the above discussion, I examine ashtanga vinyasa yoga (AVY), a major school of MPY that has greatly influenced many other forms of yoga. I point out several interpretive frameworks for a series of physical practices in ashtanga yoga (within the same school of yoga). While the Indian tradition views asanas (physical postures) as preparation for meditation, the Western counterculture-influenced yoga that developed after the late 1960s views asanas as a microcosm of life, as a search for spirituality, and as “moving meditation”.